2010
DOI: 10.3402/gha.v3i0.2142
|View full text |Cite
|
Sign up to set email alerts
|

Health status and quality of life among older adults in rural Tanzania

Abstract: BackgroundIncreasingly, human populations throughout the world are living longer and this trend is developing in sub-Saharan Africa. In developing African countries such as Tanzania, this demographic phenomenon is taking place against a background of poverty and poor health conditions. There has been limited research on how this process of ageing impacts upon the health of older people within such low-income settings.ObjectiveThe objective of this study is to describe the impacts of ageing on the health status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
68
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 32 publications
22
68
1
Order By: Relevance
“…WHODAS scores in people without dementia or MCI from the background population were similar to those of people aged 70 years and over in the Ifakara region of Tanzania (mean = 27.6) and lower than those reported from rural northern Ghana (mean 39.3) for this age group [18,20]. Comparison between studies is hampered by demographic, cultural and lifestyle factors and different methodologies used.…”
Section: Discussionmentioning
confidence: 60%
“…WHODAS scores in people without dementia or MCI from the background population were similar to those of people aged 70 years and over in the Ifakara region of Tanzania (mean = 27.6) and lower than those reported from rural northern Ghana (mean 39.3) for this age group [18,20]. Comparison between studies is hampered by demographic, cultural and lifestyle factors and different methodologies used.…”
Section: Discussionmentioning
confidence: 60%
“…Similar studies also report that the quality of life in the elderly decreased with increasing age [3,[26][27][28][29]. Certain periods of life form the basis of the differences in quality of life.…”
Section: Discussionmentioning
confidence: 68%
“…In numerous studies on the elderly, it was reported that being a woman accompanied low quality of life [26,27,29]. The low quality of life of women is an expected case just like it is for susceptibility to depression due to factors such as socio-cultural structure, the role of women in society, the role of women defined by society, their position in female-male relations as well as the changes in physiology and hormonal nature specific to women.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40] (ii) Health and functional impairments may significantly impact on older persons' quality of life. 41,42 (iii) Within the older population, levels of ill-health and impaired function clearly vary between sociodemographic (e.g., gender, rural/urban, socioeconomic) groups.…”
Section: Policy Challengesmentioning
confidence: 99%
“…41,42 (iii) Within the older population, levels of ill-health and impaired function clearly vary between sociodemographic (e.g., gender, rural/urban, socioeconomic) groups. 28,29,34,[37][38][39][40] Evidence suggests a consistently higher risk of disability, depression, dementia as well as self-reported poor health and function among older women compared to men. Findings on relationships of rural/urban and socioeconomic status to health outcomes, however, are less clear.…”
Section: Policy Challengesmentioning
confidence: 99%